Penerapan Model VARK dalam Pengelolaan Kelas untuk Meningkatkan Prestasi Siswa - Jihan Nailur Rohmah (Studi Administrasi Publik dan ilmu Komunikasi, 2024)
The application of the VARK (Visual, Auditory, Reading/Writing, Kinesthetic) model in classroom management is a strategy that can offer a more inclusive and effective approach to increasing student achievement. This research aims to explore how the use of the VARK model can improve students' learning experiences and academic performance. The research method used is a literature study, involving analysis of various relevant sources regarding the VARK concept and its application in education. The research results show that by understanding various learning preferences, educators can design learning experiences that better suit students' individual needs. Through the application of various learning strategies, such as the use of pictures and diagrams for visual students, group discussions for auditory students, reading and writing assignments for students who prefer to learn through text, as well as practical activities or experiments for kinesthetic students, students can be more involved in learning and gain a deeper understanding. This research also emphasizes the importance of flexibility in teaching, adapting to changes in student learning preferences, and evaluating the effectiveness of the learning strategies used. Although the VARK model has the advantage of providing guidance for inclusive teaching, it is important to remember that students' learning preferences may change and that various factors also influence their academic performance.